2011
DOI: 10.1089/vbz.2010.0174
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia,Ehrlichia,Anaplasma, andBartonellain Ticks and Fleas from Dogs and Cats in Bangkok

Abstract: Flea and tick specimens (5-10 fleas or ticks) on dogs and cats from various sites in Bangkok were tested by polymerase chain reaction and DNA sequencing to detect DNA of bacteria Rickettsia (gltA and 17 kDa genes), Anaplasmataceae (16S rRNA gene), and Bartonella (pap31 and its genes). We confirmed that Rickettsia sp. related to Rickettsia felis was detected in 66 of 98 (67.4%) flea specimens from dogs, whereas 8 Bartonella henselae and 2 Bartonella clarridgeiae were detected in 10 of 54 (18.5%) flea specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 25 publications
2
23
1
1
Order By: Relevance
“…This is the first report indicating the presence of the agent of Mediterranean Spotted Fever in Nigeria. Rickettsiae with ompA gene are considered to be pathogenic, while those who exclude this gene are probably non-pathogenic endosymbionts [21]. Rickettsia africae , the etiologic agent of African tick fever in humans has been detected in ticks from Nigeria [9], [10] and other West African countries [20] but not in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…This is the first report indicating the presence of the agent of Mediterranean Spotted Fever in Nigeria. Rickettsiae with ompA gene are considered to be pathogenic, while those who exclude this gene are probably non-pathogenic endosymbionts [21]. Rickettsia africae , the etiologic agent of African tick fever in humans has been detected in ticks from Nigeria [9], [10] and other West African countries [20] but not in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…For example, a partial gene of Anaplasma spp. was detected in Dermacentor auratus, Haemaphysalis lagrangei , and Amblyomma javanense collected from vertebrate hosts, including dogs, bears, and pangolins in the Thai‐Myanmar border region (Sangkhlaburi District, Kanchanaburi Province, Thailand) (Parola et al The Rickettsia ‐like Anaplasma platys has recently been identified in Rhipicephalus sanguineus ticks collected from dogs in 2011 (Foongladda et al In the present study, we report data concerning the tick species and investigate Rickettsia and Anaplasma bacteria in natural tick populations.…”
Section: Introductionmentioning
confidence: 71%
“…The results of the present study provide additional information supporting the impact of spotted fever on Thai public health (Parola et al Suttinont et al Moreover, we provided the first evidence of A. bovis in H. shimoga . However, additional Anaplasma species, such as Anaplasma platys , have been identified in Rhipicephalus sanguineus on dogs in Thailand (Foongladda et al These data suggest that domestic dogs might serve as reservoir hosts in rural areas or villages near the forest, and additional surveys and pathogen screening of tick species will increase the current understanding of the disease transmission cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although Anaplasma phagocytophilum (causative agent of human granulocytic anaplasmosis) and Ehrlichia chaffeensis (causative agent of human monocytic ehrlichiosis) have been identified in ticks from the Thai–Myanmar border and in Bangkok, to date no human data on seroprevalence or clinical disease is available for these agents (Parola et al 2003a, Foongladda et al 2011). However, one report provides serological evidence of E. chaffeensis infections in a group of healthy volunteers in western Thailand (Heppner et al 1997).…”
Section: Introductionmentioning
confidence: 99%